Unveiling the effects of consumers' psychological distance on their reactance and related behavioral outcomes: Do lockdown restrictions matter? - Chen, Xianglan; Duan, Yachao; Ittefaq, Huma; Duan, Yahui (Frontiers in Psychology, 2022)
This study examined consumers’ psychological reactance, which is insufficiently explored in the literature. This research fills the gaps found in the literature reviewed and investigates how the psychological reactance of restaurant consumers developed because of social, temporal, and spatial distancing measures during the COVID-19. This study also explored ways in which the restaurant industry can increase its compliance with COVID-19 restrictions in such a situation. We explored the effects of social, temporal, and spatial distancing on psychological reactance. We also identified the moderating effect of lockdown restrictions, which strengthen the psychological reactance developed because of (a) social distancing, (b) temporal distancing, and (c) spatial distancing. We collected data from restaurant consumers in Lahore. This study applied the quantitative techniques (i.e. test of normality, measurement model assessment, structural model assessment, and common method variance). The data analyzed using IBM SPSS 25.0 and AMOS 24.0 and the results will be interpreted and presented accordingly. This study added to the literature on psychological reactance, service management, and psychological distance. We also help the restaurant industry overcome the challenges that occurred during the COVID-19 pandemic and the closures. This study assists the restaurant industry to understand consumer behavior and attract potential consumers.